Aplikasi Sinbiotik Untuk Meningkatkan Performa Pertumbuhan Udang Vaname (Litopenaeus vannamei): Synbiotic Application To Improve Growth Performance Of Vanammei Shrimp (Litopenaeus vannamei) - Wida Lesmanawati; Widanarni; Sukenda (IPB University, 2016)
Synbiotic application shows better results compared to the single use of probiotics or prebiotics. SKT-b bacteria have been shown to act as probiotics for aquatic animals, as well as sweet potatoes that are known to act as prebiotics. This study aims to examine the synbiotic potential of SKT-b probiotic bacteria and oligosaccharide extract from sweet potato in improving the growth performance of vaname shrimp. Shrimp were treated with synbiotic feed with different prebiotic concentrations of 1% (Pro + Pre 1%), 2% (Pro + Pre 2%) and 3% (Pro + Pre 3%). The treated food was given to shrimp (weight ± 1.9 g) for 30 days. Oligosaccharides extracted from sweet potato can act as a prebiotic which increases the bacterial population in vaname shrimp’s intestine. The application of synbiotics can improve the growth performance of vaname shrimp including the addition of body weight, feed efficiency, digestive enzyme activity, protein retention and body fat of shrimp. The treatment of Pro + Pre 2% and Pro + Pre 3% shows better growth performance of vaname shrimp.